Food Security and Agrotourism: Design and Construction of Elevated Pathways to Facilitate Urban Agriculture in Wetland Areas - Mañego, Angelo; Punla Jr., Francis; Capili, Jean Carla; Benedicto, Kazeline; Fajardo, Mark Kristofer; Alcaraz, Robert Aljon (Three E Science Institute, 2024)
Food insecurity presents a critical global challenge, with developing countries disproportionately affected by its impacts. From 2020 to 2022, the Philippines reported the highest number of individuals experiencing moderate or severe food insecurity in Southeast Asia. Rapid urbanization exacerbates this problem by significantly increasing food demand in urban areas, particularly densely populated regions. As a highly urbanized locality, Malabon faces heightened risks due to its rising population and limited agricultural resources. This study addresses urban food insecurity by exploring the potential of Urban Agriculture, explicitly focusing on implementing the Baira Farming System in the wetlands of Dampalit, Malabon. Using a qualitative approach, the research involves interviewing stakeholders from the City Land Use, Planning Office, and the Local Government Unit to gather critical insights on land use policies and local socio-economic needs. Researchers perform a comprehensive review of relevant literature and conduct on-site observations to evaluate the feasibility of Urban Agriculture in urban wetland settings. By analyzing the correlation between data gathered and the unique environmental and social conditions of Dampalit, the study highlights the potential of Urban Agriculture to foster sustainable and resilient food systems in urbanized areas. This research underscores the significance of introducing accessible and adaptable agricultural practices to urban communities with limited traditional farming options. By integrating Urban Agriculture concepts, this approach addresses both food insecurity and sustainability challenges. The findings contribute valuable insights to the discourse on innovative agricultural practices, emphasizing the transformative role of sustainable solutions in mitigating food insecurity in rapidly urbanizing regions.